Faktor-Faktor yang Mempengaruhi Nyeri Punggung Ibu Hamil Trimester III: Literatur Review - Melati Nur Arummega; Alfiah Rahmawati; Arum Meiranny (Oksitosin : Jurnal Ilmiah Kebidanan, 2022)
Back pain is caused by pain in the lumbosacral area. The increase in intensity with increasing gestational age results from a shift in the center of gravity and changes in body posture. Back pain from sacroiliac/lumbar can be a long term back pain if not treated promptly. Literature review aims to examine more deeply about back pain in pregnant women in the third trimester, there were factors that influence it by reviewing. Methods literature review by searching on Google Scholar and PubMed. The keyword criteria are "pregnancy", "back pain", "low back pain pregnancy factors", "back pain pregnant women activities". After the study was conducted, national articles 9 and 15 were obtained. Factors that affect back pain in third trimester pregnant women can be classified from gestational age, age, parity, daily activities that affect back pain and body relaxation can reduce back pain . Keywords: Daily Activities, 3rd Trimester Of Pregnancy, Back Pain